Multifunctional nanocomposites of poly(vinylidene fluoride) reinforced by carbon nanotubes and magnetite nanoparticles - C. Tsonos; C. Pandis; N. Soin; D. Sakellari; E. Myrovali; S. Kripotou; A. Kanapitsas; E. Siores (eXPRESS Polymer Letters)
In the present study, the effect of nano magnetite (Fe3O4) content on structural, dielectric/electrical, magnetic and thermal properties of poly(vinylidene fluoride)/carbon nanotubes matrix, is investigated. Nanocomposite films of polyvinylidene fluoride, carbon nanotubes and Fe3O4 nanoparticles were prepared by the twin screw compounding method. Fe3O4, as magnetic inclusions was incorporated into the composites with carbon nanotubes loadings well above the percolation threshold, where conductive networks were formed. Magnetic characterization revealed the ferrimagnetic behavior of nanocomposites, with saturation magnetization values depending on magnetite content. Results obtained from the analysis of Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD) and Differential Scanning Calorimetry (DSC) techniques were very informative for the study of the polymorphism and crystallinity in PVDF. The incorporation of Fe3O4 inclusions in PVDF/CNT matrix, gradually increase both electrical conductivity and dielectric permittivity up to 10 wt% Fe3O4 content, while at the higher Fe3O4 content (15 wt%) reduced values were obtained. This behavior, at higher Fe3O4 content, should be possible related to the insulating and barrier role of Fe3O4 nanoparticles.